KONSERVASI LITERASI ANAK SEKOLAH DASAR DI LINGKUNGAN PALUH MERBAU - Lova, Stelly Martha; Suwanto, Suwanto; Lestari, Wiwik (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2024)
The community service activities carried out aim to improve students' literacy skills so that they can increase the level of education in the Paluh Merbau area. It is hoped that awareness of the importance of education can increase the knowledge of the Paluh Merbau population in dealing with technological developments. This stems from the problems faced by one of the schools in Paluh Merbau, namely MIS Raudhatul Faizin. The problems faced include: (1) The lack of teacher experience in efforts to improve students' literacy skills and (2) The lack of facilities that support students' literacy skills. The method of implementing activities is carried out through four stages, including: (1) Preparation: environmental observation (initial mapping), discussion of problems, and determination of problem solutions; (2) Implementation: implementing mentoring programs; (3) Monitoring and Evaluation: evaluation of the process and results of the mentoring program; and (4) Follow-up: developing mentoring programs in other aspects and on a wider scale. The results of the community service program that have been implemented include: (1) Assistance activities in designing learning, selecting reading sources and enjoyable reading techniques, (2) Assistance in managing and maximizing reading corners in schools, and (3) Managing and using e-books through barcode board innovation. The outcomes produced through this community service program include: (1) Teachers are able to utilize e-books in every learning design, (2) Teachers are able to manage e-books and use them, (3) Improve students' reading skills and deliver good material for teachers, (4) Availability of e-books and a management system, (5) Availability of a reading corner model, and (6) Management of reading corners and provision of reading resources (books and e-book barcode boards).